Risk Factors of Uterine Fibroid Among Patients in Hospital Selayang and Hospital Putrajaya, Malaysia - Bandarchian, Fataneh (2010)
Uterine Fibroid (UF) starts in the muscle tissues of the womb which can grow into the uterine cavity. This disease is common gynaecological disorders with numerous adverse health effects that will affect the woman’s quality of life. Since there are limited studies about risk factors of uterine fibroids in Malaysia, this case-control study aims to evaluate the proportion, presentation and management of uterine fibroid and also investigates its socio-demographic, life style, obstetrical& gynecological characteristics among Malaysian women attending Gyneacology clinics in Selayang and Putra Jaya Hospitals. In this study, based on secondary data after screening for inclusion and exclusion criteria, 752 women treated in O&G wards in the two hospitals from 2001 to 2005 were enrolled upon obtaining ethical clearance from Ethics Committee in University Putra Malaysia and the Ministry of Health Malaysia. Three hundred seventy six patients with uterine fibroid confirmed by HPE and ultrasound were recruited as cases, while a similar number of women diagnosed negative for uterine fibroid in the same clinics were recruited as controls. A structured and pre-tested proforma were used for data collection from the clinical records. Results for independent t-test revealed significant mean difference in term of age in patients with UF as compared to Non-fibroids (44.22±8.21years vs 28.54±5.60 years, p=0.001). Patients with UF were found to have less parity than women without UF (p=0.001). UF cases were more significantly found to have last child birth (LCB) of 5 years and above as compared to controls (p=0.000, OR=12.65 95% CI: 8.51-18.79). Odds ratio of occurrence of Uterine Fibroid among diabetic patients was 3.03 times more than non-diabetic patients (χ2=7.61, p=0.006, 95% CI: 1.33- 6.90). Those individuals with hypertension were 6.32 times, more likely to get uterine fibroid than individuals without hypertension (χ2=69.02, p=0.001, 95% CI: 3.94-10.14). Patients in higher socio-economic status with social class-2 were 2.19 times more likely to develop UF than women from lower socio-economic status (χ2=10.38, p=0.01, 95% CI: 1.35-3.57). Results showed a significant association between smoking and UF (χ2=6.92, p=0.01, 95% CI: 0.17-0.80). There was a significant protective association between alcoholic drinking and uterine fibroid (χ2=38.07, p=0.001, 95% CI: 0.04-0.23). Multivariate analysis concluded that higher age (adjusted OR= 1.55, 95% CI=1.42-1.68), duration of last child birth of more than 5 years (adjusted OR=4.82, 95% CI=2.26-10.29), parity (adjusted OR= 0.05, 95% CI=0.02-0.11) and alcohol consumption (adjusted OR=0.08, 95% CI=0.01-0.51) were found to contribute significantly to the risk for uterine fibroid. The findings of the present study provide an insight into risk factors that contribute to uterine fibroids among Malaysian women attending the gynecology clinics in Hospital Selayang and Hospital Putra Jaya.